Low‐Temperature Atomic Layer Deposition of High‐k SbOx for Thin Film Transistors. (4th March 2022) - Yang, Jun; Bahrami, Amin; Ding, Xingwei; Zhao, Panpan; He, Shiyang; Lehmann, Sebastian; Laitinen, Mikko; Julin, Jaakko; Kivekäs, Mikko; Sajavaara, Timo; Nielsch, Kornelius
Abstract: SbO x thin films are deposited by atomic layer deposition (ALD) using SbCl5 and Sb(NMe2 )3 as antimony reactants and H2 O and H2 O2 as oxidizers at low temperatures. SbCl5 can react with both oxidizers, while no deposition is found to occur using Sb(NMe2 )3 and H2 O. For the first time, the reaction mechanism and dielectric properties of ALD‐SbO x thin films are systematically studied, which exhibit a high breakdown field of ≈4 MV cm −1 and high areal capacitance ranging from 150 to 200 nF cm −2, corresponding to a dielectric constant ranging from 10 to 13. The ZnO semiconductor layer is integrated into a SbO x dielectric layer, and thin film transistors (TFTs) are successfully fabricated. A TFT with a SbO x dielectric layer deposited at 200 °C from Sb(NMe2 )3 and H2 O2 presents excellent performance, such as a field effect mobility ( µ ) of 12.4 cm 2 V −1 s −1, I on / I off ratio of 4 × 10 8, subthreshold swing of 0.22 V dec −1, and a trapping state ( N trap ) of 1.1 × 10 12 eV −1 cm −2 . The amorphous structure and high areal capacitance of SbO x boosts the interface between the semiconductor and dielectric layer of TFT devices and provide a strong electric field for electrons to improve the device mobility. Abstract : SbO x thin films deposited by atomic layer deposition shows a high areal capacitance of 200 nF cm −2, corresponding to a dielectric constant of 13. The amorphous structure and high areal capacitance of SbO x boosts the interface between the semiconductor and dielectric layer of thin film transistor devices and provide a strong electric field for electrons to improve the device mobility.